An Explorative Study of Affiliate Stigma, Resilience, and Quality of Life Among Parents of Children with Autism Spectrum Disorder (ASD) - Noor Suhada, Salleh; Tang, Li Yoong; Subhashini, Jayanath; Khatijah Lim, Abdullah * (Dove Press, 2022)
Purpose: Children diagnosed with ASD usually have impaired social functions, exhibit repetitive, stereotyped and self-stimulatory behaviors, which make them prone to be stigmatized by the public. However, stigma not only affects those with stigmatization characteristics such as children with ASD but also tends to include other people related to them including parents. This is called affiliate stigma. However, affiliate stigma is unlikely to occur if public awareness is high. Considering that awareness of ASD is still comparatively low in this region and that, as a review of the literature showed, there have been limited studies on stigma and ASD conducted in South-East Asia, particularly in Malaysia, this study is of great significance, especially in the context of the East and other developing countries. The aim of this study was to explore parents' experiences of caring and perceptions of affiliate stigma, resilience and quality of life (QoL) when caring for a child with ASD.